Work -Life Balance and Work Stress in Work Environment -A Study - M. , Bagirathi; V. , Nalini (International Journal of Psychosocial Rehabilitation, 2020)
Work-life balance is a crucial aspect of a healthy work environment. Maintaining work-life balance helps reduce stress and helps prevent burnout in the workplace. The term “work-life balance” has yet to lose its buzz in the last few years. This is partially due to the dominating presence of millennials in the workforce. Employers have been putting in a tremendous effort trying to determine the best way to appeal to millennial workers. Workplace stress is a big deal. While you would possibly think that stressed employees are the norm, it’s important to know that stress can cause some serious health consequences. As an employer, one of your many responsibilities is to take care of your employees and keep their well-being a priority. Chronic stress is one of the most common health issues in the workplace. It can lead to physical consequences such as hypertension, digestive troubles, chronic aches and pains, and heart problems. Chronic stress can also negatively impact mental health because it’s linked to a higher risk of depression, anxiety, and insomnia. Too much stress over an extended period of your time results in workplace burnout. Employees who work plenty of overtime hours are at a high risk of burnout. Burnout can cause fatigue, mood swings, irritability, and a decrease in work performance. By creating an environment that prioritizes work-life balance, employers can economize and maintain a healthier, more productive workforce. But what exactly does work-life balance look like? Well, that’s where things can get a bit complicated. Work-life balance means something a touch different to everyone. Over the years, the knowledge and approach of work-life balance have been constantly evolving, and it’d be helpful for employers to spot the difference in opinions among the Baby Boomers, Generation X, and Millennials. Besides the physical effects of stress—like high vital signs, body aches, and heart issues—these bad health habits can also translate into poor work performance. Stressed-out employees have trouble focusing, thinking clearly, and making rational decisions. While it’s not reasonable to expect a business to function properly with zero workplace stress, employers got to recognize the red flags of overly stressed employees and know when to take things down a notch. Preventing and helping employees manage stress will keep your employees healthier, happier, and more productive.